Determinasi Kinerja Keuangan Sektor Strategis di Indonesia - Palupi, Devia Galuh; Nariman, Augustpaosa (Penerbit Goodwood, 2025)
Purpose: This study aims to provide empirical evidence on the effect of carbon emission disclosure, green investment, and leverage on corporate financial performance. Methodology/approach: The research sample includes companies in the basic materials, energy, and property & real estate sectors listed on the Indonesia Stock Exchange during the 2022–2023 period. The sample was selected using purposive sampling, and the data were analyzed using multiple linear regression. Results/findings: The findings indicate that carbon emission disclosure, green investment, and leverage have a significant impact on a company's financial performance. The concludes of this study indicate that firms engaging in public disclosure of carbon emissions and exhibiting high leverage ratios are likely to experience diminished financial performance. In contrast, the disclosure of green investment initiatives appears to positively contribute to enhancing a firm's financial outcomes. Conclusions: The study finds carbon disclosure and leverage negatively impact financial performance, while green investment has a positive effect. Limitations: This research employs independent variables that remain limited in relation to environmental factors, and the observation period covers only a short duration, which may not be sufficient to adequately capture their influence on financial statements Contribution: This research is expected to enrich the academic literature on the relationship between sustainability aspects and financial performance. It may also serve as a reference for corporate management, particularly in the basic material, energy serta property & real estate sectors, in formulating sustainability strategies that not only fulfill regulatory and social requirements but also have a positive impact on the company’s financial performance.